Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Evaluating ecological and socio-economic system dimensions to improve fisheries management in the Bohai Sea, China - Jie Yin; Jia Wo; Yunzhou Li; Ming Sun; Jacob G. Eurich; Kristin M. Kleisner; Shems B. Jud; Yi Tang; Shu Su; Yaping Ao; Yong Chen (Reviews in Fish Biology and Fisheries, 2026)

Botulinum toxin injection combined with rehabilitation training for peroneal spastic flatfoot: A pilot case series - Ran Zhang; Yaping Chen; Xiuying Huang; Yuxin Tian; Lu Wang (Toxicon, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Supplemental vitamins A, D, and E improve OPU-IVP efficiency in postpartum dairy cows by alleviating oxidative stress - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Conserved and specific roles of photoperiod and circadian rhythm-related genes on flowering time in Lotus japonicus - Wang Yihan; Dai Xinglong; Liu Jiao; Liu Yujuan; Chen Siping; He Yijun; Chen Chen; Jiang Huawu; Kong Fanjiang; Chen Yaping (Plant Science, 2026)

Integrated prediction of rainfall-induced landslides using zone parameterization and physical-based probabilistic modelling - Renwen Liu; Wei Zhou; Yaping Zhou; Huaqiang Yin; Ming Chen (Geomorphology, 2026)

Bamboo cellulose fiber aerogel for radioactive cobalt adsorption with ultimate volume reduction: A green and economic disposal pathway - Hongyan Chen; Zhuo Chen; Zhanquan Wang; Yu Wang; Xinyu Xie; Qin Chen; Jinchao Li; Yaping Zhang; Liang Chen (Chemical Engineering Journal, 2026)

Anomalous thermally enhanced output and ion-exchange repairability of flame-retardant waste cotton textile-based triboelectric nanogenerators - Kun Zhao; Yaping Liu; Li Chen; Mengdan Shen; Xuefeng Lu; Yuandong Li; Yong Wang; Kewei Zhang (Chemical Engineering Journal, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Exercise-induced neuropeptidergic and neurochemical neuroadaptation in stress regulation and emotional disorders - Ziqi Wang; Zhinei Tan; Yaping Zhang; Yuzhou Li; Jinyan Lin; Yingli Xu; Yongxia Li; Ting Chen (Acta Neurologica Belgica, 2026)

Combined CO₂ and topographic uplift forcing on vegetation and climate change in the North China Plain since ∼6.5 Ma - Wei Liu; Likang Wang; Zhenjing Yang; Dianbao Chen; Dexuan Chen; Yaping Li; Xiaozhong Huang; Yunfa Miao; Baotian Pan (Global and Planetary Change, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Subduction-dominated processes control deep lithospheric structure and microplate tectonics of the Iranian Plateau: Insights from multi-geophysical inversions - Feiyu Zhao; Sanzhong Li; Junling Pei; Yanhui Suo; Mengxue Dai; Shengxing Zhang; Xiao Chen; Yanguo Wang; Yaping Hu; Bin Hu (Earth-Science Reviews, 2026)

GnRH supplementation in the PreOvsynch protocol targeting follicular cysts enhances synchronization and reduces days open in dairy cows - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Animal Reproduction Science, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Bifurcation and phase desynchronization of vortex-induced vibration in a cable–buoy system under wave-induced parametric excitation - Yaobing Zhao; Yaping Liu; Qiang Wen; Qiufu Xie; Lincong Chen (Ocean Engineering, 2026)

Multiscale discrete fracture-matrix method for simulating groundwater flow in fractured geological media - Chen Zuo; Lei Ma; Di Gao; Qiankun Luo; Yaping Deng; Jiazhong Qian (Journal of Hydrology, 2026)

Seismic rock-physics inversion for petrophysical parameters in deep coalbed methane reservoirs with complex pore structures - Qiang Guo; Yang Chen; Yaping Huang; Jing Ba (Journal of Applied Geophysics, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Bisphenol A exposure disrupts the circadian clock system and impairs glycolipid metabolic function in mice liver - Hao Dong; Wenli Ding; Bonan Xiao; Cuimei Li; Haizhen Jiang; Wanghao Yang; Dan Li; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; et al. (Food and Chemical Toxicology, 2026)

Fluid–structure interaction training of integral conservation physics-informed neural networks for blood flow in elastic vessels - Youqiong Liu; Li Cai; Yaping Chen; Qingsheng Liu (Computer Physics Communications, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

A real-world pharmacovigilance study of dacomitinib based on FDA adverse event reporting system (FAERS) database - Yuqin Yang; Yaping Huang; Yifan Wang; Chengjie Ke; Maohua Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Dynamic changes in rainfall thresholds for post-seismic debris flows using logistic regression and resampling - Renwen Liu; Wei Zhou; Huaqiang Yin; Yaping Zhou; Ming Chen (Bulletin of Engineering Geology and the Environment, 2026)

From syngas to food - high-moisture extrusion of Clostridium autoethanogenum protein into fibrous meat analogues - Tao Ding; Zhougang Chen; Yuchen Zhao; Hao Wang; Xiaofang Liang; Jie Wang; Jie Yang; Yaping Zhu; Shifeng Ma; Min Xue (Food Research International, 2026)

Elevated oxygen partial pressure reduces population exposure to hypoxia over the Qinghai–Xizang Plateau - Yanqiang Chen; Ying Zhang; Yaping Wang; Qinmei Han; Gangfeng Zhang; Xiaoyue Liu; Peijun Shi; Cunrui Huang (Science Bulletin, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

Rainfall patterns and catchment characteristics interactively regulate nitrogen and phosphorus dynamics in agricultural ponds - Hengbin Xiao; Yaping Chen; Tianzi Hu; Ronggui Hu (CATENA, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Urban land surface temperature prediction by integrating LSTM and geospatial information: A case study of Kunming, China - Ronghui Li; Yaping Zhang; Xu Chen (Journal of Cleaner Production, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Enhancing Kiwifruit (Actinidia spp.) Growth Through a Microbial Consortia in Alkali Soil - Xiao Shu; Yixiao Fan; Shuai Shen; Yaping Chen (Journal of Soil Science and Plant Nutrition, 2026)

Postmarketing adverse events of biologics and Janus kinase inhibitors in patients with atopic dermatitis - Yaping Huang; Qing Zhou; Chengjie Ke; Maohua Chen (Inflammopharmacology, 2026)

Hierarchical PBO/Mica/MOF-303 composite films for tri-functional triboelectric nanogenerators: Enhanced charge density, flame retardancy, and humidity resistance - Yaping Liu; Mengdan Shen; Yuan Ye; Chaohui Zhang; Li Chen; Kun Zhao (Chemical Engineering Journal, 2026)

Effects of thermal alkaline hydrolysis and biochar addition on anaerobic digestion of sewage sludge and fate of antibiotic resistance genes - Ruoxin Li; Chunsheng Qiu; Xu Chen; Nannan Liu; Yaping Zhang; Li Qi; Shaopo Wang (Bioresource Technology, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Resveratrol can inhibit porcine reproductive and respiratory syndrome virus infection in vitro and in vivo by inhibiting PI3K/Akt signaling pathway - Yaping Chen; Wenshuang Chen; Xinqi Song; Xinyi Zhao; Li Yang; Ruoyu Zhao; Meilong Song; Bingbing Zhang; Dongbo Sun (Veterinary Microbiology, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

A quantitative assessment framework for ship collision risk: Integrating spatiotemporal urgency analysis - Yu Chen Xin; Xiong Guan Bao; Yaping Yang (Ocean Engineering, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Effects of roads on animals and mitigation measures in Asia - Haotong Su; Yun Wang; Qilin Li; Yangang Yang; Abudusaimaiti Maierdiyali; Shuangcheng Tao; Yaping Kong; Jiding Chen; Jiapeng Qu; Yongshun Han; Aili Kang; Shu Chen; et al. (Biological Conservation, 2026)

Effect of thermal alkaline and thermal hydrolysis on the methane production and antibiotic resistance genes removal during sewage sludge anaerobic digestion - Ruoxin Li; Chunsheng Qiu; Nannan Liu; Wen Zhang; Xu Chen; Yaping Zhang; Chenchen Wang; Shaopo Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Immunotoxicity and effects of gut microbiota in chicks exposed to low doses of deoxynivalenol and 15-acetyl-deoxynivalenol - Wandi Bu; Xinyao Wu; Zhihang Zhong; Yaping Fang; Shuang Chen; Jun Jiang; Yiqun Deng (Toxicology and Applied Pharmacology, 2025)

Future climate change exacerbates streamflow depletion in the Wei River Basin, China - Hongli Chen; Lijing Fan; Qiang Li; Yaping Wang; Dengfeng Liu; Fubo Zhao (Journal of Hydrology, 2025)

BFlow and Eckhardt methods perform best among non-tracer-based baseflow separation methods - Qiaoqiao Wang; Qiang Li; Yanli Qin; Xuanjiao Chai; Hongli Chen; Yaping Wang; Mingfang Zhang; Dengfeng Liu (Journal of Hydrology, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Elucidation of antibacterial efficacy and mechanism of the extract from fruit of Phyllanthus emblica L. against Vibrio cholerae and Staphylococcus aureus - Fengfeng Cao; Yue Liu; Enyu Tian; Yaping Wang; Shunlin Ren; Yongjie Wang; Huajun Zheng; Lanming Chen (Food Control, 2025)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Lanthanide-based MOFs with metal-node-modulated energy transfer for multifunctional X-ray imaging platforms - Chenrui Wang; Haitao Li; Jiankun Xue; Yaping Chen; Lian Wang; Xieming Xu; Shuaihua Wang; Rong Li (Chemical Engineering Journal, 2025)

Impacts of nitrate on methane production and microbial communities in paddy soil - Wenjia Zhao; Lang Liu; Zhidong Liang; Jian Sun; Yi Wang; Hua Chen; Yaping Zhang; Yong Yuan (Journal of Soils and Sediments, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

A multi-algorithm fusion approach for identifying post-earthquake rainfall-induced debris flow catchments - Huaqiang Yin; Wei Zhou; Renwen Liu; Yaping Zhou; Ming Chen; Zhangqiang Peng (Bulletin of Engineering Geology and the Environment, 2025)

Transcription factor OxyR regulates peroxidase levels to enhance Brucella's defense against oxidative stress - Yunyi Zhai; Hui Wang; Guangdong Zhang; Bin Li; Ziyang Diao; Lei Chen; Lulu Tian; Feijie Zhi; Junmei Li; Dong Zhou; Wei Liu; Yaping Jin; et al. (Veterinary Microbiology, 2025)

Impact of transient flow on bimolecular reactive transport in varying-aperture fractures - Yajing Liu; Jiazhong Qian; Yong Liu; Lei Ma; Yaping Deng; Hailong Chen (Journal of Hydrology, 2025)

Testing and applying analytical depletion functions for multiple pumping wells in two hydrogeological landscapes - Lijing Fan; Hongli Chen; Qiang Li; Kunpeng Li; Yaping Wang (Journal of Hydrology, 2025)

Environmental variables affect the effectiveness of ecosystem services of ecological restoration project: Evidence from Xiangjiang River Basin-Dongting Lake - Shu Fu; Jianjun Zhang; Yufei Li; Wei Chen; Yaping Zhang; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2025)

Environmental tobacco smoke exposure in pregnant women and thyroid hormone levels in newborn cord blood: A birth cohort in China - Tengwei Gui; Yan Li; Yaping Liu; Jirong Li; Tong Luo; Shuqi Chen; Xiaoxiao Song; Xia Xiao (Environmental Pollution, 2025)

Robust topology optimization of multi-material structure with load uncertainty based on element-free Galerkin method - Jianping Zhang; Tao Chen; Jiahong Chen; Xuemei Peng; Yaping Zhao; Haishan Lu; Dabing Zhang (Engineering Structures, 2025)

Bio-inspired spore-like CoSe2@CNFs heterostructure enabling ultra-stable and high-rate sodium-ion batteries - Enze Ren; Yu Chen; Yaping Zeng; Zhenyao Wang; Wanquan Liu; Heng Wang; Jianrong Xiao; Liu Wang (Chemical Engineering Journal, 2025)

Fine root length density and production surpass root exudates to shape soil aggregate stability in a warm-temperate natural oak forest under multi-year drought conditions - Xiaomin Gao; Xiuqing Nie; Yi Wang; Cuiju Liu; Yaping Di; Zhicheng Chen; Baoliang Niu; Shirong Liu (Plant and Soil, 2025)

Alamandine inhibits pathological retinal neovascularization by targeting the MrgD-mediated HIF-1α/VEGF pathway - Kun Zhao; Yaping Jiang; Wen Huang; Yukang Mao; Yihui Chen; Peng Li; Chuanxi Yang (Journal of Zhejiang University-SCIENCE B, 2025)

Assessment for the wildlife crossing structures along the Qinghai-Tibet railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Mei Luo; Xueyang Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Hao Wang; Zhi Lu (Transportation Research Part D: Transport and Environment, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Electro-enhanced adsorption and ionization-promoted hydrolysis for 3-cyanopyridine in high-salinity wastewater: Process optimization and mechanistic insights - Yaping Guo; Xinhua Huang; Hongying Chen; Mengyao Ren; Xiang Liu; Xiaoxiao Zhai; Kanming Wang (Journal of Water Process Engineering, 2025)

Fabric-based composite membrane for simultaneous emulsion separation and self-powered real-time monitoring - Chengcheng Li; Chengjian Yao; Keru Hou; Jie Wang; Peibo Du; Jinping Zhang; Yinjie Chen; Xing Su; Yaping Zhao; Zaisheng Cai (Journal of Hazardous Materials, 2025)

Antibacterial photodynamic inactivation of pH-responsive microspheres based on chitosan/carboxymethyl chitosan with hypericin and its application in food preservation - Jingyi He; Sai Zhang; Zeyu Hu; Hetong Chen; Yaping Wang; Kewei Feng; Junfeng Yao; Yahong Yuan; Tianli Yue; Qinglin Sheng (Food Bioscience, 2025)

Unraveling the chrono-regulatory function of PhoP in nitrogen metabolism: A multi-scale engineering framework aimed at optimizing the synthesis of poly-γ-glutamic acid in Bacillus licheniformis - Qing Zhang; Shisi He; Zhihao Zhu; Fangzhou Cheng; Yaping Jin; Wanying Zhu; Fan Yang; Yaozhong Chen; Mengyuan Zhang; Xin Li; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

Mutation in maize chloroplastic polypeptide chain release factor (ZmcpRF1) affects chloroplast development and leaf color - Hao Chen; Haixiao Dong; Xiaohui Shan; Yuan Jiang; Shipeng Li; Hongkui Liu; Shengzhong Su; Yaping Yuan (Planta, 2025)

Inversion of aboveground biomass of Spartina alterniflora based on multispectral UAV - Ziyao Chen; Yan Gu; Jianchun Chen; Dingchen Liu; Junjie Rui; Shibing Zhu; Yaping Wang (Acta Oceanologica Sinica, 2025)

Global Non-site Regional Visibility Seasonal Forecast Integrating Geographical Distance - Shuaiwen Wu; Siyu Chen; Yaping Shao; Yue Zhang; Wenhan Li; Shasha Qiao (Aerosol Science and Engineering, 2025)

The interspecies relationships among the wildlife crossing structures of the Qinghai-Tibet Railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Zhi Lu (Journal for Nature Conservation, 2025)

Effect of labor migration on famers’ biopesticide application --mediating effect based on social network - Ruixin Zhang; Yexing Yin; Yushi Chen; Jinyang Sun; Yuying Liu; Xinhong Fu; Yaping Wang (Environment, Development and Sustainability, 2025)

Glyphosate exposure impairs glucose and lipid metabolism by disturbing the circadian clock system in mice liver - Bonan Xiao; Haizhen Jiang; Hao Dong; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; Huatao Chen (Food and Chemical Toxicology, 2025)

Progress on the mechanism of natural polysaccharides in the treatment of arthritis - Lili Yuan; Michael Adu-Frimpong; Hong Chen; Yaping Yang; Jiangnan Yu; Huiya Wang; Yuxiang He; Elmurat Toreniyazov; Xia Cao; Qilong Wang; Ximing Xu (Inflammopharmacology, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

Response of ecological condition in ecologically fragile areas to disturbance from extreme precipitation event: An empirical analysis from the loess plateau - Kexin Yi; Jianjun Zhang; Haoyi Lei; Wei Chen; Yaping Zhang; Shu Fu; Ke Wang (Journal of Cleaner Production, 2025)

ICPINN: Integral conservation physics-informed neural networks based on adaptive activation functions for 3D blood flow simulations - Youqiong Liu; Li Cai; Yaping Chen; Qixing Chen (Computer Physics Communications, 2025)

Synthesis of a novel tricarboxylic acid monomer and construction of branched polybenzimidazole membranes for vanadium redox flow battery - Huiting Li; Jun Long; Wenheng Huang; Xiyang Liu; Jinchao Li; Liang Chen; Qin Chen; Qianqian Liang; Zhengjin Yang; Yaping Zhang (Chemical Engineering Journal, 2025)

Enhanced nitrogen and phosphorus removal from actual domestic sewage using a novel ecological AAO process integrated with natural zeolite and vegetation - Zhiqiang Wang; Hua Chen; Jian Sun; Xingwen Lu; Yao He; Yujie Wang; Yaping Zhang; Renli Liang (Journal of Water Process Engineering, 2025)

Temporal and spatial changes of ungulate activity before and after the construction of the Qinghai-Tibet railway in Hoh Xil, China - Abudusaimaiti Maierdiyali; Yun Wang; Yangang Yang; Shuangcheng Tao; Yaping Kong; Jiding Chen; Xin Yang; Basanglamao; Hao Wang; Zhi Lu (Journal of Transport Geography, 2025)

The effect of removing bound polyphenols on the physicochemical and functional properties of Rosa roxburghii tratt dietary fiber in vitro - Xiaoli Zhou; Zhicheng Qin; Yan Chen; Yaping Wang; Dong Lin; Lingshuai Meng (Food Bioscience, 2025)

Deep learning-based inversion framework for fractured media characterization by assimilating hydraulic tomography and thermal tracer tomography data: Numerical and field study - Cihai Chen; Yaping Deng; Jiazhong Qian; Haichun Ma; Lei Ma; Jichun Wu; Hui Wu (Engineering Geology, 2025)

Improving resilience to extreme heat events through green space morphology: A threshold-based perspective - Yixin Dai; Jianjun Zhang; Shu Fu; Wei Chen; Yaping Zhang; Kexin Yi (Sustainable Cities and Society, 2025)

Vegetation and climate dynamics in Southwestern China during the Han and Jin Dynasties (202 BC-AD 420): Insights from the Spore-pollen and hydrological records from the Chengba site - Junna Zhang; Liu Qi; Yaping Li; Weidong Chen; Luhong Zheng; Xueran Wang; Songhan Li; Bingyuan Zhang (Quaternary International, 2025)

Impact of Drought on Farmers’ Livelihood Vulnerability: A Case Study of County-level Units in Western Jilin Province, China - Jiani Zhang; Yang Han; Yangang Fang; Yaping Xu; Chunlin Chen; Zhuxin Liu; Feiyu Wang; Lijuan Zhuang; Fang Huang (Chinese Geographical Science, 2025)

Role of Bacillus atrophaeus B1 in gut on nicotine tolerance of the fall armyworm - Yaping Chen; Wenyuan Zhao; Yanfang Hu; Yao Chen; Yahong Li; Zhongxiang Sun; Yuerui Li; Rongchao Luo; Ewei Du; Furong Gui (Pesticide Biochemistry and Physiology, 2025)

Research on the spatial correlation network and its driving factors for synergistic development of pollution reduction, carbon reduction, greening, and growth in China's tourism industry - Ying Li; Shizhuan Hao; Yaping Liu; Beilei Chen; Tongqian Zou (Journal of Environmental Management, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

Detection of small foreign objects in Pu-erh sun-dried green tea: An enhanced YOLOv8 neural network model based on deep learning - Zejun Wang; Shihao Zhang; Yaping Chen; Yuxing Xia; Houqiao Wang; Ronghua Jin; Chun Wang; Zongpei Fan; Yuefei Wang; Baijuan Wang (Food Control, 2025)

Synergistic effects of carbon and heat under disturbance of human activities: Evidence from a resource-based city of China - Yaping Zhang; Jianjun Zhang; Wei Chen; Sen Liang; Kexin Yi; Shidong Liu (Environmental Pollution, 2025)

A new evolutionary topology optimization method for truss structures towards practical design applications - Yaping Lai; Qi Cai; Yu Li; Jiayong Chen; Yi Min Xie (Engineering Structures, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

The influences of climate factors on net primary productivity of Gannan grassland, the Qinghai-Tibet Plateau, China - Yaping Hua; Yufei Wei; Long Chen (Theoretical and Applied Climatology, 2025)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

Global patterns of lake microplastic pollution: Insights from regional human development levels - Dan Chen; Ping Wang; Shiqi Liu; Rui Wang; Yaping Wu; A-Xing Zhu; Chunnuan Deng (Science of The Total Environment, 2024)

Early-onset familial essential tremor is associated with nucleotide expansions of spinocerebellar ataxia in China - Zhilin Zheng; Zeyu Zhu; Jiali Pu; Chen Zhou; Lanxiao Cao; Dayao Lv; Jinyu Lu; Gaohua Zhao; Yanxing Chen; Jun Tian; Xinzhen Yin; Baorong Zhang; et al. (Molecular Biology Reports, 2024)

Effects of LAZY family genes on shoot gravitropism in Lotus japonicus - Shaoming Xu; Shusi Song; Huawu Jiang; Guojiang Wu; Yaping Chen (Plant Science, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Rill erosion and controlling factors on highway side-slopes in the permafrost region - Rui Li; Lilei Wu; Longxi Cao; Yaping Kong; Guo Chen; Ting Wu (Journal of Mountain Science, 2024)

Multi-omics analysis reveals anthocyanin synthesis is associated with drought stress tolerance in Chaenomeles speciosa flowers - Shuangyu Zhang; Xiling Chen; Yanshen Ren; Xingyue Xue; Yaping Xu; Qi Wang; Yanru Xie; Tengxun Zhang; Jiayi Lin; Xiaolu Chen; Houhua Li (Journal of Cleaner Production, 2024)

Heating pattern and effects of built-up land in response to influencing factors: A statistical estimation of 172 Chinese cities - Wei Chen; Jianjun Zhang; Yaping Zhang; Shu Fu; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2024)

The nature of synergy effects between VO and TiO2 in low temperature NH3-SCR reaction - Yingying Jin; Jiaying Li; Kaihao Fan; Yong Chen; Yaping Yang; Xuesong Liu (Journal of Environmental Chemical Engineering, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Release of bound phenol from Rosa roxburghii pomace via solid-state fermentation with Trichoderma viride: Mechanisms of change - Yanli Wang; Yaping Wang; Xiaoli Zhou; Bin Du; Yan Chen (Food Bioscience, 2024)

Deep eutectic solvent microemulsions with abundant hydrogen ions in supercritical CO2 for decontamination of radioactive solid waste: Overcoming roadblocks to hydrogen ions deficiency - Huitao Lv; Jianzhang Gao; Jiaqi Chen; Tianyu Li; Chao Peng; Yaping Li; Fuqiu Ma; Yun Xue; Yongde Yan; Emmanuel Osei Tutu (Chemical Engineering Journal, 2024)

SNCA is a potential therapeutic target for COVID-19 infection in diffuse large B-cell lymphoma patients - Can Chen; Yun Li; Yiwei Li; Zhenzhen Chen; Pengfei Shi; Yaping Xie; Shenxian Qian (Apoptosis, 2024)
Cuprotosis related genes (CRGs) have been proved to be potential therapeutic targets for coronavirus disease 2019 (COVID-19) and cancer, but their immune and molecular mechanisms in COVID-19 infection in Diffuse Large B-cell Lymphoma (DLBC/DLBCL) patients are rarely reported. Our research goal is first to screen the key CRGs in COVID-19 through univariate analysis, machine learning and clinical samples. Secondly, we determined the expression and prognostic role of key CRGs in DLBCL through pan-cancer analysis. We validated the expression levels and prognosis using multiple datasets and independent clinical samples and validated the functional role of key CRGs in DLBCL through cell experiments. Finally, we validated the expression levels of CRGs in COVID-19 infected DLBCL patients samples and analyzed their common pathways in COVID-19 and DLBCL. The results show that synuclein-alpha (SNCA) is the common key differential gene of COVID-19 and DLBCL. DLBCL cells confirm that high expression of SNCA can significantly promote cell apoptosis and significantly inhibit the cycle progression of DLBCL. High expression of SNCA can regulate the binding of major histocompatibility complexes (MHCs) and T cell receptor (TCR) by regulating immune infiltration of Dendritic cells, effectively enhancing T cell-mediated anti-tumor immunity and clearing cancer cells. In conclusion, SNCA may be a potential therapeutic target for COVID-19 infection in DLBCL patients. Our study provides a theoretical basis for improving the clinical treatment of COVID-19 infection in DLBCL patients.

Therapeutic Effect of Smilax glabra Roxb. on Weaning Rats Against Pb-Induced Nephrotoxicity Based on Network Pharmacology - Chongmei Tian; Meiting Yu; Yuejuan Fang; Yaping Zhao; Liping Fu; Jingbai Chen; Daozong Xia (Biological Trace Element Research, 2024)

Electroacupuncture Ameliorates Neuronal Damage and Neurological Deficits after Cerebral Ischemia-Reperfusion Injury via Restoring Telomerase Reverse Transcriptase - Dan Chen; Yunxia Xiang; Di Wu; Hui Wang; Yaping Huang; Hongbo Xiao (Cell Biochemistry and Biophysics, 2024)

Effect of maternal cigarette smoke exposure on COPD progression in offspring mice - Jiawei Sun; Huan Chen; Xu Xu; Yaping Dou; Baofa Wu; Hongyang Zhang; Song Shang; Wuzhuang Sun (Reproductive Toxicology, 2024)

Role of Enterococcus mundtii in gut of the tomato leaf miner (Tuta absoluta) to detoxification of Chlorantraniliprole - Yao Chen; Yaping Chen; Yibo Zhang; Zhongxiang Sun; Yahong Li; Jiasheng Ding; Guifen Zhang; Ewei Du; Xiaoyan Zi; Chaoxin Tian; Wenyuan Zhao; Furong Gui (Pesticide Biochemistry and Physiology, 2024)

Seasonal dynamics, tidal influences, and anthropogenic impacts on microplastic distribution in the Yangtze River estuary: A comprehensive characterization and comparative analysis - Panfeng Wu; Yuchuan Fan; Xinxin Zhang; Wei Wu; Zaifeng Zhang; Yaping Wu; Jingyi Wang; Jing Xu; Tianming Chen; Bin Gao (Journal of Hazardous Materials, 2024)

A grazing crab drives saltmarsh carbon storage and recovery - Serina S. Wittyngham; David Samuel Johnson; Yaping Chen; Matthew L. Kirwan (Ecology, 2024)
Consumers can directly (e.g., consumption) and indirectly (e.g., trophic cascades) influence carbon cycling in blue carbon ecosystems. Previous work found that large grazers have nuanced effects on carbon stocks, yet, small, bioturbating‐grazers, which remove plant biomass and alter sediment properties, remain an understudied driver of carbon cycling. We used field‐derived and remote sensing data to quantify how the purple marsh crab, Sesarma reticulatum , influenced carbon stocks, flux, and recovery in salt marshes. Sesarma caused a 40%–70% loss in carbon stocks as fronts propagated inland (i.e., ungrazed to recovered transition), with front migration rates accelerating over time. Despite latitudinal differences, front migration rate had no effect on carbon stocks, flux, or time to replacement. When we included Sesarma disturbance in carbon flux calculations, we found it may take 5–100 years for marshes to replace lost carbon, if at all. Combined, we show that small grazers cause a net loss in carbon stocks as they move through the landscape, and irrespective of migration rate, these grazer‐driven impacts persist for decades. This work showcases the significant role of consumers in carbon storage and flux, challenging the classic paradigm of plant–sediment feedbacks as the primary ecogeomorphic driver of carbon cycling in blue carbon ecosystems.

Effect of Fe2+-activated persulfate combined with biodegradation in removing gasoline BTX from karst groundwater: A box-column experimental study - Yaping Jiang; Renqian Lu; Yudao Chen; Ritian Deng; Xu Deng (Environmental Science and Pollution Research, 2024)

Effects of nanoplastic exposure during pregnancy and lactation on neurodevelopment of rat offspring - Lei Tian; Yaping Zhang; Jiang Chen; Xuan Liu; Huipeng Nie; Kang Li; Huanliang Liu; Wenqing Lai; Yue Shi; Zhuge Xi; Bencheng Lin (Journal of Hazardous Materials, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

Isolation and structural characterization of flavonoids from E Se tea and their synergistic inhibitory effects on lipid accumulation via regulating AMPK/ACC pathway - Jiaxiong Zhang; Jinke Zhang; Xiaoqian Wang; Taiming Chen; Zhengxuan Wang; Yaping Liu; Guiguang Cheng (Food Bioscience, 2024)

A simulation system to study the types and causes of browning in concentrated orange juice during storage - Yangyang Chen; Min Zhang; Arun S. Mujumdar; Yaping Liu (Food and Bioproducts Processing, 2024)

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Cardiac toxicity of brentuximab vedotin: a real-word disproportionality analysis of the FDA Adverse Event Reporting System (FAERS) database - Chengjie Ke; Maohua Chen; Yaping Huang; Yan Chen; Cuihong Lin; Pinfang Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Evaluation of the effect of road barriers on wildlife habitats - Yangang Yang; Yun Wang; Hongping Zhou; Xueping Chen; Shuangcheng Tao; Yaping Kong (Transportation Research Part D: Transport and Environment, 2024)

Spartina alterniflora invasion benefits blue carbon sequestration in China - Jingfan Zhang; Dehua Mao; Jihua Liu; Yaping Chen; Matthew Kirwan; Christian Sanders; Jinge Zhou; Zhe Lu; Guoming Qin; Xingyun Huang; Hui Li; Hengqi Yan; et al. (Science Bulletin, 2024)

Empirical investigation of parameter impacts on the three-dimensional coefficient of restitution of jujube at the time of harvest - Shiqi Yao; Shiguan An; Zhiye Bai; Shan Chen; Za Kan; Hewei Meng; Li Yaping (Postharvest Biology and Technology, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Efficient production of R-2-(4-hydroxyphenoxy) propionic acid by Beauveria bassiana using biofilm-based two-stage fermentation - Shuping Zou; Yizhi Ma; Wei Ding; Yongkang Jiang; Xiaomin Chen; Juan Chen; Hailing Gao; Yaping Xue; Yuguo Zheng (Bioresource Technology, 2024)

Distribution and source of heavy metals in Tibetan Plateau topsoil: New insight into the influence of long-range transported sources to the surrounding glaciers - Xiaoli Liu; Wenhua Gao; Ting Wei; Zhiwen Dong; Jiawen Ren; Yaping Shao; Xuejiao Chen (Environmental Pollution, 2024)

Multi-objective migrating birds optimization for solving stochastic home health care routing and scheduling problems considering caregiver working time constraints - Yaping Fu; Xiaomeng Ma; Kaizhou Gao; Hongfeng Wang; Ali Sadollah; L.Y. Chen (Swarm and Evolutionary Computation, 2024)

Relationship of environmental exposure temperature and temperature extremes on sperm DNA fragmentation index in men with different BMI values and the indirect effect of DNA fragmentation index on semen parameters - Chen Wang; Qiwei Yu; Ting Chu; Fang Wang; Fangli Dong; Hang Xin; Di Wang; Yaping Liu; Jun Zhai (Science of The Total Environment, 2024)

Effects of elevated CO2 and spinetoram on the population fitness and detoxification enzymes activities in Frankliniella occidentalis and F. intonsa - Zongfang Fan; Yaping Chen; Rui Fan; Bin Chen; Lei Qian; Furong Gui (Journal of Pest Science, 2024)

Correction to: Compensatory Mechanisms Absorb Regional Carbon Losses Within a Rapidly Shifting Coastal Mosaic - Alexander J. Smith; Karen McGlathery; Yaping Chen; Carolyn J. Ewers Lewis; Scott C. Doney; Keryn Gedan; Carly K. LaRoche; Peter Berg; Michael L. Pace; Julie C. Zinnert; Matthew L. Kirwan (Ecosystems, 2024)

Baicalin − 2- ethoxyethyl ester alleviates renal fibrosis by inhibiting PI3K/AKT/NF-κB signaling pathway - Jiacun Li; Ke Zhang; Mei Xu; Huanyue Cui; Yaping Guo; Dahong Yao; Wenhua Chen; Huaimin Liang; Hangyu Wang; Jinhui Wang (Toxicology and Applied Pharmacology, 2024)

Large contributions of emission reductions and meteorological conditions to the abatement of PM2.5 in Beijing during the 24th Winter Olympic Games in 2022 - Yaping Jiang; Shaocai Yu; Xue Chen; Yibo Zhang; Mengying Li; Zhen Li; Zhe Song; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Journal of Environmental Sciences, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Functional characterization of polyol/monosaccharide transporter 1 in Lotus japonicus - Leru Liu; Shaoming Xu; Lu Tian; Xuelian Qin; Guojiang Wu; Huawu Jiang; Yaping Chen (Journal of Plant Physiology, 2024)

Effects of urban renewal on green space: Evidence from airborne particulate matter in a mega city cluster - Zhenyu Zhang; Chongchong Zhu; Long Wang; Yaping Chen (Journal of Cleaner Production, 2024)

Fisetin, a dietary flavonoid, promotes transintestinal cholesterol excretion through the activation of PPARδ - Yao Guo; Bing Liu; Yaping Geng; Ke Chen; Junyan Li; Xiangju Yin; Shenshen Zhang (Food Research International, 2024)

Reproductive hormones, organophosphate esters and semen quality: Exploring associations and mediation effects among men from an infertility clinic - Yaping Li; Zhiyi Zheng; Dan Luo; Chong Liu; Sijie Yang; Yingjun Chen; Qian Hu; Wenqing Lu; Yixin Wang; Surong Mei (Environmental Research, 2024)

Folate-modified carboxymethyl chitosan-based drug delivery system for breast cancer specific combination therapy via regulating mitochondrial calcium concentration - Yonggang Lv; Xi Chen; Yaping Shen (Carbohydrate Polymers, 2024)

Compensatory Mechanisms Absorb Regional Carbon Losses Within a Rapidly Shifting Coastal Mosaic - Alexander J. Smith; Karen McGlathery; Yaping Chen; Carolyn J. Ewers Lewis; Scott C. Doney; Keryn Gedan; Carly K. LaRoche; Peter Berg; Michael L. Pace; Julie C. Zinnert; Matthew L. Kirwan (Ecosystems, 2024)

Upland forest retreat lags behind sea‐level rise in the mid‐Atlantic coast - Yaping Chen; Matthew L. Kirwan (Global Change Biology, 2024)
Ghost forests consisting of dead trees adjacent to marshes are striking indicators of climate change, and marsh migration into retreating coastal forests is a primary mechanism for marsh survival in the face of global sea‐level rise. Models of coastal transgression typically assume inundation of a static topography and instantaneous conversion of forest to marsh with rising seas. In contrast, here we use four decades of satellite observations to show that many low‐elevation forests along the US mid‐Atlantic coast have survived despite undergoing relative sea‐level rise rates (RSLRR) that are among the fastest on Earth. Lateral forest retreat rates were strongly mediated by topography and seawater salinity, but not directly explained by spatial variability in RSLRR, climate, or disturbance. The elevation of coastal tree lines shifted upslope at rates correlated with, but far less than, contemporary RSLRR. Together, these findings suggest a multi‐decadal lag between RSLRR and land conversion that implies coastal ecosystem resistance. Predictions based on instantaneous conversion of uplands to wetlands may therefore overestimate future land conversion in ways that challenge the timing of greenhouse gas fluxes and marsh creation, but also imply that the full effects of historical sea‐level rise have yet to be realized.

Osthole protects H9c2 cardiomyocytes against trastuzumab-induced damage by enhancing autophagy through the p38MAPK/mTOR signaling pathway - Huan Hou; Yaping Yang; Rong Chen; Zhiping Guo (Toxicology in Vitro, 2023)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

Cytotoxic 4-phenylcoumarins from the flowering buds of Mesua ferrea - Xiya Chen; Zhiying Liu; Bi Zhong; Mengjie Zhu; Han Yao; Xiaojie Chen; Yongchao Lu; Shuyun Wang; Yaping Guo (Natural Product Research, 2023)

Characteristics and mechanism of phosphate removal by lanthanum modified bentonite in the presence of dissolved organic matter - Mingxin Zhang; Yaping Zhang; Xi Chen; Jian Sun; Xingwen Lu; Yao He; Yujie Wang (Chemosphere, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Research progress on pharmacological effects and mechanisms of cepharanthine and its derivatives - Liangliang Shi; Shuaizhe Wang; Shangzu Zhang; Jiawei Wang; Yaping Chen; Yangyang Li; Zhiwei Liu; Sichen Zhao; Benjun Wei; Liying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

ALPK1 Expressed in IB4-Positive Neurons of Mice Trigeminal Ganglions Promotes MIA-Induced TMJ pain - Taomin Zhu; Huimin Li; Yuxiang Chen; Xueke Jia; Xiaohan Ma; Xin Liu; Yaping Feng; Jin Ke (Molecular Neurobiology, 2023)

NR1 Splicing Variant NR1a in Cerebellar Granule Neurons Constitutes a Better Motor Learning in the Mouse - Ting Tan; Linyan Jiang; Zhengxiao He; Xuejiao Ding; Xiaoli Xiong; Mingxi Tang; Yuan Chen; Yaping Tang (The Cerebellum, 2023)
As an excitatory neuron in the cerebellum, the granule cells play a crucial role in motor learning. The assembly of NMDAR in these neurons varies in developmental stages, while the significance of this variety is still not clear. In this study, we found that motor training could specially upregulate the expression level of NR1a, a splicing form of NR1 subunit. Interestingly, overexpression of this splicing variant in a cerebellar granule cell-specific manner dramatically elevated the NMDAR binding activity. Furthermore, the NR1a transgenic mice did not only show an enhanced motor learning, but also exhibit a higher efficacy for motor training in motor learning. Our results suggested that as a “junior” receptor, NR1a facilitates NMDAR activity as well as motor skill learning.

Neoproterozoic subduction-related active rifting in the South China Craton: insights from geochemical and zircon Hf isotopic data - Weizhen Tian; Guanghui Wu; Yaping Wang; Yang Shuai; R. Damian Nance; Xiaojun Zhou; Hakro Ahmed Suhail; Chen Zhang; Bo Zheng (International Geology Review, 2023)

Downregulation of XBP1s aggravates lipopolysaccharide-induced inflammation by promoting NF-κB and NLRP3 pathways’ activation in goat endometrial epithelial cells - Kangkang Gao; Yanyan Yi; Zhongqiang Xue; Zongjie Wang; Shan Huang; Beibei Zhang; Pengfei Lin; Aihua Wang; Huatao Chen; Yaping Jin (Theriogenology, 2023)

Enhancing efficiency of biological contact oxidation reactors through filaments optimization of basalt fibers bio-carriers: Insights from a pilot-scale study - Huicheng Ni; Muhammad Arslan; Tiancai Zhang; Lizhuang Chen; Yaping Wang; Junchao Qian; Fu Cao; Zhiren Wu; Mohamed Gamal El-Din (Journal of Water Process Engineering, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Effect of pore-throat structure on air-foam flooding performance in a low-permeability reservoir - Guangfeng Liu; Yaping Ding; Juntao Wang; Lizhen Ge; Xiaoming Chen; Daoyong Yang (Fuel, 2023)

Establishment of a halotolerant bioremediation platform from Halomonas cupida using synthetic biology approaches - Wanwan Zhao; Weini Xiong; Yujie Liu; Hongfu Guo; Siqi Wang; Yaping Chen; Ruihua Liu; Bingzhi Li; Chao Yang (Chemical Engineering Journal, 2023)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

How can new-energy vehicle companies use organizational resilience to build business ecological advantages? The role of ecological niche and resource orchestration - Yaping Xie; Ruijun Chen; Jiru Cheng (Journal of Cleaner Production, 2023)

Acceleration of Fe3+/Fe2+ cycle in garland-like MIL-101(Fe)/MoS2 nanosheets to promote peroxymonosulfate activation for sulfamethoxazole degradation - Ke Zhu; Wenlei Qin; Yaping Gan; Yizhe Huang; Zhiwei Jiang; Yuwen Chen; Xin Li; Kai Yan (Chemical Engineering Journal, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Influencing mechanism and hydrogeological implications of water level fluctuation of lakes in the northern Qaidam Basin, Qinghai-Tibet Plateau - Yaping Cheng; Qishun Fan; Tianyuan Chen; Haotian Yang; Qingkuan Li; Chunmei Han (Journal of Oceanology and Limnology, 2023)

Ecological risk assessment of potentially toxic elements in selenium-rich soil with different land-use types - Jinming Zhang; Wen Ge; Chen Xing; Yuan Liu; Xiaofei Shen; Bing Zhao; Xinyu Chen; Yaping Xu; Shoubiao Zhou (Environmental Geochemistry and Health, 2023)

One‐kilometre monthly air temperature and precipitation product over the Mongolian Plateau for 1950–2020 - Ying Xin; Yaping Yang; Xiaona Chen; Xiafang Yue; Yangxiaoyue Liu; Cong Yin (International Journal of Climatology, 2023)
The fragile ecological environment of the Mongolian Plateau (MP) is sensitive to climate change. It is necessary to fully understand the temperature and precipitation changes on the MP to ensure regional sustainable development. Most existing studies are conducted based on station observations which suffer from sparse distribution and limited spatial representativeness and cannot perfectly represent the climatic conditions of the whole region. By contrast, the long‐term, spatially continuous reanalysis products offer new opportunities for MP climate change research. However, the coarse spatial resolution and large uncertainties of reanalysis data limit their applicability to provide reliable climate information at finer scales. Within the delta downscaling framework, we downscale and correct the state‐of‐the‐art European Centre for Medium‐range Weather Forecasts ReAnalysis 5 land portion (ERA5‐Land) using a high‐resolution WorldClim reference climatology and generate a long‐term (1950–2020) 1‐km monthly air temperature and precipitation downscaled dataset. During the downscaling process, the results obtained by nearest neighbour, bilinear and bicubic interpolation methods are evaluated and compared. Air temperature result of bilinear method and precipitation result of nearest neighbour method, which have the best accuracy, are taken as the final downscaled data. The evaluation shows that the downscaled data has acceptable accuracy (overall MBE = −0.41°C, Corr = 0.997, RMSE = 1.51°C for air temperature, and MBE = 1.58 mm·month −1 , Corr = 0.747, RMSE = 24.24 mm·month −1 for precipitation), and outperforms the original ERA5‐Land and widely used Climatic Research Unit (CRU) data. In addition, the downscaled data can also provide accurate and detailed temperature and precipitation change trends over the MP. With fine spatial resolution, long‐time span and good spatial continuity, the downscaled air temperature and precipitation will be a useful data source to explore climate change over the MP.

In situ confined growth of g-C3N4/pigment compound catalyst in porous diatomite for enhancing photocatalytic nicotine elimination and bacterial inactivation - Junting Gao; Zhijing Wu; Yaping Wang; Yunjin Zhong; Feng Gao; Wenxing Chen; Wangyang Lu (Journal of Environmental Chemical Engineering, 2023)

Corrigendum to ‘Polyvinyl alcohol/starch-based film incorporated with grape skin anthocyanins and metal-organic framework crystals for colorimetric monitoring of pork freshness ‘[Food Chem. 395 (2022) 133613] - Xueqi Lin; Ning Li; Qiao Xiao; Yaping Guo; Jie Wei; Tianhui Jiao; Qingmin Chen; Quansheng Chen; Xiaomei Chen (Food Chemistry, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Mapping nighttime PM2.5 concentrations in Nanjing, China based on NPP/VIIRS nighttime light data - Huijuan Chen; Yongming Xu; Sheng Zhong; Yaping Mo; Shanyou Zhu (Atmospheric Environment, 2023)

Design, synthesis and biological evaluation of aminopyrimidine derivatives bearing dihydroquinoxalinone as novel EGFRL858R/T790M kinase inhibitors against non-small-cell lung cancer - Liping Fu; Yu Cao; Jingbai Chen; Ruoyu He; Yanmei Zhao; Yaping Zhao; Jianjun Xi; Rangxiao Zhuang; Chongmei Tian (Medicinal Chemistry Research, 2023)

Distribution of benthic macrofaunal communities in intertidal flat under hydrodynamic influence: a case study of Jiangsu coast, East China - Longhui Zhang; Dezhi Chen; Shu Gao; Yaping Wang; Benwei Shi; Yongfen Du (Journal of Oceanology and Limnology, 2023)

Origin, composition, and accumulation of dissolved organic matter in a hypersaline lake of the Qinghai-Tibet Plateau - Yaoling Zhang; Keli Yang; Hongmei Chen; Yaping Dong; Wu Li (Science of The Total Environment, 2023)

Anthropogenic drought in the Yellow River basin: Multifaceted and weakening connections between meteorological and hydrological droughts - Yaping Wang; Shuai Wang; Yanqiang Chen; Fei Wang; Yanxu Liu; Wenwu Zhao (Journal of Hydrology, 2023)

Freight transport structure evaluation and optimization toward sustainable development: New evidence from the SBM-DEA model with undesirable outputs - Rujia Chen; Yaping Zhang (Environment, Development and Sustainability, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

The spatial configuration of buildings: A vital consideration impossible to ignore in regulating urban land surface temperature? Evidence from 35 Chinese cities - Wei Chen; Jianjun Zhang; Shidong Liu; Sen Liang; Yaping Zhang; Shu Fu (Science of The Total Environment, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Improved thermal tolerance of ovotransferrin against pasteurization by phosphorylation - Yaping Liu; Jiajie Wang; Chenxin Huang; Bingying Cai; Fuxuan Guo; Lin Chen; Xianchao Feng; Meihu Ma (Food Chemistry, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Conceptual design of long span steel-UHPC composite network arch bridge - Yaping Lai; Yu Li; Maoke Huang; Lijun Zhao; Jiayong Chen; Yi Min Xie (Engineering Structures, 2023)

Assessing freight structure and its effect on transport CO2 emissions: heterogeneous and mediating effect analysis - Rujia Chen; Yaping Zhang (Environmental Science and Pollution Research, 2023)

3D natural fracture model of shale reservoir based on petrophysical characterization - Yaping Li; Xiaowei Chen; Yongbo Shao (Journal of Structural Geology, 2023)

Fabrication and characterization of l-ascorbyl palmitate and phospholipid-based hybrid liposomes and their impacts on the stability of loaded hydrophobic polyphenols - Mianhong Chen; Ruyi Li; Xuli Lu; Yaping Dai; Tinghui Chen; Yuhang Xing; Lu Xue; Zhihao Duan; Wei Zhou; Jihua Li (Food Chemistry, 2023)

Spatial and temporal characteristics of nighttime UHII based on local climate zone scheme using mobile measurement-A case study of Changsha - Yaping Chen; Jiayu Li; Yinze Hu; Luyun Liu (Building and Environment, 2023)

Parameter identification and state estimation for nuclear reactor operation digital twin - Helin Gong; Tao Zhu; Zhang Chen; Yaping Wan; Qing Li (Annals of Nuclear Energy, 2023)

The nonlinear effect of land freight structure on carbon emission intensity: new evidence from road and rail freight in China - Rujia Chen; Xiaoning Wang; Yaping Zhang; Qian Luo (Environmental Science and Pollution Research, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Urolithin A inhibits enterovirus 71 replication and promotes autophagy and apoptosis of infected cells in vitro - Shengyu Wang; Junhua Qiao; Yaping Chen; Langfei Tian; Xin Sun (Archives of Virology, 2022)

Dynamic Damping-Based Terminal Sliding Mode Event-Triggered Fault-Tolerant Pre-Compensation Stochastic Control for Tracked ROV - Qiyu Chen; Yancai Hu; Qiang Zhang; Junpeng Jiang; Mingshan Chi; Yaping Zhu (Journal of Marine Science and Engineering, 2022)
Due to the unknown disturbance caused by the harsh environment in deep water, the stability of Underwater Tracked Remotely Opreated Vehicle (UTROV) trajectory tracking control is affected; especially the resistance forces of random vibrations caused by non-differentiable random disturbance resistance, which has become one of the main problems in controller design. Considering engineering practice, a stochastic model and new dynamic damping-based terminal sliding mode event-triggered fault-tolerant controller were designed in this paper. Firstly, based on the random resistance pre-compensation theory for the first time, a stochastic model was designed for differential drive UTROV. Meanwhile, a new nonsingular terminal sliding mode and dynamic damping reaching law were designed to achieve global finite-time convergence and reduce chattering with better robust response speed. Furthermore, to deal with the wear and tear caused by actuator failure and fixed sampling rate transmission, a new dynamic event trigger mechanism was designed and the faults analyzed. On this basis, combined with the finite-time adaptive on-line estimation technology, it can not only better reduce the transmission frequency, but also the finite-time dynamic active fault-tolerant compensation. The control scheme has semi-globally finite-time stability in probability and is proved by theory, which is compliant with engineering requirements. Then, according to characteristics of innovation, the three groups of simulation of control methods are designed to compare the methods in this paper. Finally the advantages of the method are verified by simulation to achieve the design expectations.

A New Dual-peak Fluorescent Probe for Water Content Detection Made From Taxus - Gang Wang; Yaping Li; Haipeng Chen; Shuqin Tang; Yiyang Cheng; Yuhong Yu; Abdul Qayoom Majeedano; Shangrao Pu; Gang Wang (Journal of Fluorescence, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Jun Wang; Xuexia Zhu; Yunfei Sun; Lei Gu; Yaping Wu; Yafen Chen; Zhou Yang (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus ( T. obscurus ), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.

Preferential removal of benzene, toluene, ethylbenzene, and xylene (BTEX) by persulfate in ethanol-containing aquifer materials - Huan Wang; Yudao Chen; Wei Meng; Yaping Jiang; Yaping Cheng (Environmental Science and Pollution Research, 2022)

Enhancement of oral bioavailability and anti-hyperuricemic activity of aloe emodin via novel Soluplus®—glycyrrhizic acid mixed micelle system - Feng Shi; Lin Chen; Yaping Wang; Jing Liu; Michael Adu-Frimpong; Hao Ji; Elmurat Toreniyazov; Qilong Wang; Jiangnan Yu; Ximing Xu (Drug Delivery and Translational Research, 2022)

A multi-stage supply chain disruption mitigation strategy considering product life cycle during COVID-19 - Jingze Chen; Hongfeng Wang; Yaping Fu (Environmental Science and Pollution Research, 2022)

Metabolite profiling in albino tea mutant Camellia sinensis ‘Fuyun 6’ using LC–ESI–MS/MS - Xinying Lin; Xuejin Chen; Pengjie Wang; Yucheng Zheng; Yongchun Guo; Yaping Hong; Ruxing Yang; Naixing Ye (Trees, 2022)

Correction: Feasibility of nitrate reduction combined with persulfate oxidation in the remediation of groundwater contaminated by gasoline - Huan Wang; Yudao Chen; Lewei He; Yaping Jiang; Yuan Xia; Pengfei Yang (Hydrogeology Journal, 2022)

Feasibility of nitrate reduction combined with persulfate oxidation in the remediation of groundwater contaminated by gasoline - Huan Wang; Yudao Chen; Lewei He; Yaping Jiang; Yuan Xia; Pengfei Yang (Hydrogeology Journal, 2022)

A 90-Day Subchronic Toxicity Study of Consumption of GH-Transgenic Triploid Carp in Wistar Rats - Jingya Guo; Yongming Li; Yaping Wang; Boyong Chen; Yingxin Hu; Yasheng Musha; Xiaoyun He; Tao Tong; Kunlun Huang (Fishes, 2022)
Genetic modification (GM) offers an alternative strategy to conventional animal breeding. The present study was carried out to investigate the potential health effects of the consumption of growth hormone-transgenic triploid carp (GH-ttc) through a 90-day subchronic rodent feeding study. Wistar rats (n = 10/sex/group) were given formulated diets containing GH-ttc or non-GM carp at an incorporated rate of 2.5%, 5%, or 10% (w/w) for 90 days. An additional control group of rats (n = 10/sex/group) was fed a basic rodent diet. During the 90-day study, clinical observation, ophthalmic examination, body weight, and food intake were evaluated. At the end of the study, rats were killed, and the hematology, serum chemistry, urine test, necropsy, and histopathology were assessed. Compared with the non-GM carp and the basic control groups, no biologically significant differences were observed on clinical signs of toxicity, body weights, food intake, hematology, serum chemistry, urinalysis, organ weight, and histopathology on selected organs for the GH-ttc group. The results of this 90-day subchronic feeding study indicated that, at the dose level used in this study, consumption of GH-ttc showed no subchronic toxicity to Wistar rats.

Spring snow depth changes and feedback to surface air temperature across the Tibetan plateau from 1961 to 2013 - Xiaona Chen; Yaping Yang (International Journal of Climatology, 2022)
Spring snow depth (SSD) in the Tibetan Plateau (TP) plays an essential role in snow water estimation, vegetation growth, and climate projections for Southwest China and the surrounding Asian countries. Previous studies have reported a decline in SSD that is associated with increasing surface air temperature ( T s ) across the TP over the past decades. However, only a few studies have explored the potential feedback of SSD to T s , which has hindered the elucidation of the vulnerability of snow cover in the TP against the backdrop of rapid climate change. Based on data from 69 meteorological stations in the central and eastern parts of the TP, this study analyses changes in SSD and its feedback to T s from 1961 to 2013. Overall, a slightly negative trend in SSD was observed from 1961 to 2013, during which two contrasting trends were detected using a piecewise regression approach: an initial increase from 1961 to 1981 (0.12 cm decades −1 , p −1 , p T s anomaly, with sensitivities of −0.050 cm °C −1 ( p −1 ( p T s was attenuated, with averaged feedback values from −1.328°C cm −1 during 1961–2013 to −0.936°C cm −1 during 1982–2013 in latitudes below 3,500 m, distributed in the Qaidam and Yellow River basins, and the upper reaches of the Yangtze River basin. The decrease in feedback from SSD to T s may lead to changes in the mechanism controlling T s dynamics across the TP, which should be considered in climate change projections in future studies.

Preparation and performance evaluation of novel magnetic porous carriers in fluidized bed bioreactor for wastewater treatment - Qibang Tong; Guixin Wang; Maolian Chen; Yaping Chen; Yong Guo (Biodegradation, 2021)

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

The inhibitory effects of the antifouling compound Irgarol 1051 on the marine diatom Skeletonema sp. across a broad range of photosynthetically active radiation - Yao Tang; Cheng Chen; Yangjie Sheng; Peijian Ding; Xinyu Wu; John Beardall; Yaping Wu (Environmental Science and Pollution Research, 2021)

Anaerobic semi-fixed bed biofilm reactor (An-SFB-BR) for treatment of high concentration p-nitrophenol wastewater under shock loading conditions - Maolian Chen; Ningning Yu; Yaping Chen; Qibang Tong; Yong Guo (Biodegradation, 2021)

Fast one-step preparation of porous carbon with hierarchical oxygen-enriched structure from waste lignin for chloramphenicol removal - Aixia Chen; Jiaju Pang; Xiao Wei; Bei Chen; Yaping Xie (Environmental Science and Pollution Research, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

Effects of UV-modified biochar derived from phytoremediation residue on Cd bioavailability and uptake in Coriandrum sativum L. in a Cd-contaminated soil - Yaping Zhang; Zhenyan Chen; Chunhong Chen; Fangzhou Li; Kai Shen (Environmental Science and Pollution Research, 2021)

Cotton seedling drought tolerance is improved via salt preconditioning - Rong Fan; Xiujuan Su; Yaping Guo; Fenglei Sun; Yanying Qu; Quanjia Chen (Protoplasma, 2021)

Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (Plant Molecular Biology, 2021)

Divergent shrub‐cover responses driven by climate, wildfire, and permafrost interactions in Arctic tundra ecosystems - Yaping Chen; Feng Sheng Hu; Mark J. Lara (Global Change Biology, 2021)
The expansion of shrubs across the Arctic tundra may fundamentally modify land–atmosphere interactions. However, it remains unclear how shrub expansion pattern is linked with key environmental drivers, such as climate change and fire disturbance. Here we used 40+ years of high‐resolution (~1.0 m) aerial and satellite imagery to estimate shrub‐cover change in 114 study sites across four burned and unburned upland (ice‐poor) and lowland (ice‐rich) tundra ecosystems in northern Alaska. Validated with data from four additional upland and lowland tundra fires, our results reveal that summer precipitation was the most important climatic driver ( r = 0.67, p p r = 0.83, p 2 ha −1 , ~7 times the amount identified in adjacent unburned upland tundra (155.1 ± 55.4 m 2 ha −1 ). In contrast, shrub cover markedly decreased in lowland tundra after fire disturbance, which triggered thermokarst‐associated water impounding and resulted in 52.4% loss of shrub cover over three decades. No correlation was found between lowland shrub cover with fire severity ( r = 0.01). Mean summer air temperature (MSAT) was the principal factor driving lowland shrub‐cover dynamics between 1951 and 2007. Warmer MSAT facilitated shrub expansion in unburned lowlands ( r = 0.78, p r = −0.82, p

Conditional Deletion of Foxg1 Alleviates Demyelination and Facilitates Remyelination via the Wnt Signaling Pathway in Cuprizone-Induced Demyelinated Mice - Fuxing Dong; Dajin Liu; Feiyu Jiang; Yaping Liu; Xiuxiang Wu; Xuebin Qu; Jing Liu; Yan Chen; Hongbin Fan; Ruiqin Yao (Neuroscience Bulletin, 2021)
The massive loss of oligodendrocytes caused by various pathological factors is a basic feature of many demyelinating diseases of the central nervous system (CNS). Based on a variety of studies, it is now well established that impairment of oligodendrocyte precursor cells (OPCs) to differentiate and remyelinate axons is a vital event in the failed treatment of demyelinating diseases. Recent evidence suggests that Foxg1 is essential for the proliferation of certain precursors and inhibits premature neurogenesis during brain development. To date, very little attention has been paid to the role of Foxg1 in the proliferation and differentiation of OPCs in demyelinating diseases of the CNS. Here, for the first time, we examined the effects of Foxg1 on demyelination and remyelination in the brain using a cuprizone (CPZ)-induced mouse model. In this work, 7-week-old Foxg1 conditional knockout and wild-type (WT) mice were fed a diet containing 0.2% CPZ w/w for 5 weeks, after which CPZ was withdrawn to enable remyelination. Our results demonstrated that, compared with WT mice, Foxg1 -knockout mice exhibited not only alleviated demyelination but also accelerated remyelination of the demyelinated corpus callosum. Furthermore, we found that Foxg1 knockout decreased the proliferation of OPCs and accelerated their differentiation into mature oligodendrocytes both in vivo and in vitro . Wnt signaling plays a critical role in development and in a variety of diseases. GSK-3β, a key regulatory kinase in the Wnt pathway, regulates the ability of β-catenin to enter nuclei, where it activates the expression of Wnt target genes. We then used SB216763, a selective inhibitor of GSK-3β activity, to further demonstrate the regulatory mechanism by which Foxg1 affects OPCs in vitro . The results showed that SB216763 clearly inhibited the expression of GSK-3β, which abolished the effect of the proliferation and differentiation of OPCs caused by the knockdown of Foxg1 . These results suggest that Foxg1 is involved in the proliferation and differentiation of OPCs through the Wnt signaling pathway. The present experimental results are some of the first to suggest that Foxg1 is a new therapeutic target for the treatment of demyelinating diseases of the CNS.

Assessing the effects of oyster/kelp weight ratio on water column properties: an experimental IMTA study at Sanggou Bay, China - Jinghui Fang; Jianguang Fang; Qionglin Chen; Yuze Mao; Zengjie Jiang; Meirong Du; Yaping Gao; Fan Lin (Journal of Oceanology and Limnology, 2020)

Degradation of recalcitrant organic matter in SAARB leachate by a combined process of coagulation and catalytic ozonation - Yan Xiang; Yaping Chen; Siqiang Luo; Junliang Zou; Aiping Zhang (Environmental Science and Pollution Research, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Generation of mice with hepatocyte-specific conditional deletion of sphingosine kinase 1 - Jinfeng Yu; Jiale Dong; Kangdi Chen; Yaping Ding; Zhicheng Yang; Tian Lan (Transgenic Research, 2020)

A microcosm study on persulfate oxidation combined with enhanced bioremediation to remove dissolved BTEX in gasoline-contaminated groundwater - Yuan Xia; Yaping Cheng; Liuyue Li; Yudao Chen; Yaping Jiang (Biodegradation, 2020)

Effect of ionic liquid [MIm]HSO4 on WPCB metal-enriched scraps refined by slurry electrolysis - Yaping Qi; Xiaoxia Yi; Yugai Zhang; Fansong Meng; Jiancheng Shu; Furong Xiu; Zhi Sun; Shuhui Sun; Mengjun Chen (Environmental Science and Pollution Research, 2019)

Myelin Oligodendrocyte Glycoprotein-IgG Contributes to Oligodendrocytopathy in the Presence of Complement, Distinct from Astrocytopathy Induced by AQP4-IgG - Ling Fang; Xinmei Kang; Zhen Wang; Shisi Wang; Jingqi Wang; Yifan Zhou; Chen Chen; Xiaobo Sun; Yaping Yan; Allan G. Kermode; Lisheng Peng; Wei Qiu (Neuroscience Bulletin, 2019)

Enhanced Phytoextraction for Co-contaminated Soil with Cd and Pb by Ryegrass (Lolium perenne L.) - Yaping Zhang; Fangzhou Li; Weiwei Xu; Jinghua Ren; Sihui Chen; Kai Shen; Zhen Long (Bulletin of Environmental Contamination and Toxicology, 2019)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Response of Yesso scallop Patinopecten yessoensis to acute temperature challenge: physiological and biochemical parameters - Weiwei Jiang; Meirong Du; Jianguang Fang; Yaping Gao; Yuze Mao; Qionglin Chen; Fan Lin; Zengjie Jiang (Journal of Oceanology and Limnology, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

Population genetic patterns of the solitary tunicate, Molgula manhattensis, in invaded Chinese coasts: large-scale homogeneity but fine-scale heterogeneity - Yiyong Chen; Shiguo Li; Yaping Lin; Hongjun Li; Aibin Zhan (Marine Biodiversity, 2018)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Air pumping for alleviation of heavy smog in Beijing - Yaping Shao; Sven Ulbrich; Dehui Chen (Science China Earth Sciences, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

Elucidating the molecular mechanism of the inhibitory effect of epigallocatechin-3-gallate on Microcystis aeruginosa - Jin Wang; Chen Dai; Xiaoqian Zhang; Yaping Lu (Journal of Applied Phycology, 2018)

Stocks and dynamics of particulate and dissolved organic matter in a large, shallow eutrophic lake (Taihu, China) with dense cyanobacterial blooms - Limei Shi; Yaxin Huang; Yaping Lu; Feizhou Chen; Min Zhang; Yang Yu; Fanxiang Kong (Journal of Oceanology and Limnology, 2018)

Association of genetic variations in RTN4 3′-UTR with risk for clear cell renal cell carcinoma - Yan Pu; Peng Chen; Bin Zhou; Peng Zhang; Yanyun Wang; Yaping Song; Lin Zhang (Familial Cancer, 2018)

Analysis of the characteristics of offshore currents in the Changjiang (Yangtze River) estuarine waters based on buoy observations - Peng Li; Benwei Shi; Yaping Wang; Weihua Qin; Yangang Li; Jian Chen (Acta Oceanologica Sinica, 2017)

Quantitative proteomics analysis reveals the tolerance of Mirabilis jalapa L. to petroleum contamination - Shuisen Chen; Hui Ma; Zhifu Guo; Yaping Feng; Jingwei Lin; Menghua Zhang; Ming Zhong (Environmental Science and Pollution Research, 2017)

Genome-wide analysis of the terpene synthase gene family in physic nut (Jatropha curcas L.) and functional identification of six terpene synthases - Wangdan Xiong; Pingzhi Wu; Yongxia Jia; Xiaoyi Wei; Liangxiong Xu; Yanfang Yang; Deyou Qiu; Yaping Chen; Meiru Li; Huawu Jiang; Guojiang Wu (Tree Genetics & Genomes, 2016)

Ginsenoside Rg1 protects human umbilical cord blood-derived stromal cells against tert-Butyl hydroperoxide-induced apoptosis through Akt–FoxO3a–Bim signaling pathway - Ying Liu; Long Yi; Lu Wang; Linbo Chen; Xiongbin Chen; Yaping Wang (Molecular and Cellular Biochemistry, 2016)

Luman recruiting factor is involved in stromal cell proliferation during decidualization in mice - Xiao Li; Pengfei Lin; Fenglei Chen; Nan Wang; Fan Zhao; Aihua Wang; Yaping Jin (Cell and Tissue Research, 2016)

Partitioning of Dichloro-diphenyl-trichloroethane and Its Metabolites Between Artificial Solid Media and Air - Yaping Zhang; Erping Bi; Honghan Chen (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Removal of Trace As(V) from Water with the Titanium Dioxide/ACF Composite Electrode - Liang Peng; Yaping Chen; Hong Dong; Qingru Zeng; Huijuan Song; Liyuan Chai; Ji-dong Gu (Water, Air, & Soil Pollution, 2015)

Development and characterization of 16 polymorphic microsatellite markers for the highly invasive ascidian, Ciona savignyi - Ping Ni; Yaping Lin; Yiyong Chen; Haitao Li; Yan Zhao; Aibin Zhan (Conservation Genetics Resources, 2015)

Removal of trace Cd(II) from water with the manganese oxides/ACF composite electrode - Yaping Chen; Liang Peng; Qingru Zeng; Yang Yang; Ming Lei; Huijuan Song; Liyuan Chai; Jidong Gu (Clean Technologies and Environmental Policy, 2015)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

soil-air partitioning of polychlorinated biphenyls and total dichloro-diphenyl-trichloroethanes - Yaping Zhang; Erping Bi; Honghan Chen (Journal of Earth Science, 2014)

GRP78 expression and regulation in the mouse uterus during embryo implantation - PengFei Lin; YaPing Jin; XiangLi Lan; YanZhou Yang; Fenglei Chen; Nan Wang; Xiao Li; YuJie Sun; AiHua Wang (Journal of Molecular Histology, 2014)

Comparative proteomic and physiological analysis of diurnal changes in Nostoc flagelliforme - Wenyu Liang; Lingxia Wang; Yaping Zhang; Xiaoting Lei; Jia Yang; Xiangrong You; Chi-Lien Cheng; Youwen Zhou; Wei Chen (Journal of Applied Phycology, 2013)

Observational climatology and characteristics of wintertime atmospheric blocking over Ural–Siberia - Ho Nam Cheung; Wen Zhou; Yaping Shao; Wen Chen; Hing Yim Mok; Man Chi Wu (Climate Dynamics, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Antigenic analysis of grass carp reovirus using single-chain variable fragment antibody against IgM from Ctenopharyngodon idella - CongLin Chen; XiaoYun Sun; LanJie Liao; ShaoXiang Luo; ZhouQuan Li; XiaoHua Zhang; YaPing Wang; QionLin Guo; Qin Fang; HePing Dai (Science China Life Sciences, 2013)

Downregulation of Cinnamoyl CoA Reductase Affects Lignin and Phenolic Acids Biosynthesis in Salvia miltiorrhiza Bunge - Zhengjun Wang; Langjun Cui; Chen Chen; Xiaojing Liu; Yaping Yan; Zhezhi Wang (Plant Molecular Biology Reporter, 2012)

Influence of Eight Unclassified Missense Variants of the MLH1 Gene on Lynch Syndrome Susceptibility - Yimei Fan; Jinyun Chen; Wei Wang; Puyuan Wu; Wenxian Zhi; Binshuang Xue; Wanfen Zhang; Yaping Wang (Biochemical Genetics, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Overexpression of NYGGF4 (PID1) induces mitochondrial impairment in 3T3-L1 adipocytes - Yaping Zhao; Chunmei Zhang; Xiaohui Chen; Chunlin Gao; Chenbo Ji; Fukun Chen; Chun Zhu; Jingai Zhu; Jialin Wang; Lingmei Qian; Xirong Guo (Molecular and Cellular Biochemistry, 2010)

SOCS-1 is a central mediator of steroid-increased thymocyte apoptosis and decreased survival following sepsis - Chun-Shiang Chung; Yaping Chen; Patricia S. Grutkoski; Lesley Doughty; Alfred Ayala (Apoptosis, 2007)

Cloning and expression of peroxisomal Ascorbate Peroxidase gene from wheat - Yaping Chen; Huazhong Wang; Xiue Wang; Aizhong Cao; Peidu Chen (Molecular Biology Reports, 2006)

Mutational analysis of the mitochondrial 12S rRNA gene in Chinese pediatric subjects with aminoglycoside-induced and non-syndromic hearing loss - Zhiyuan Li; Ronghua Li; Jianfu Chen; Zhisu Liao; Yi Zhu; Yaping Qian; Sudao Xiong; Selena Heman-Ackah; Jianbo Wu; Daniel I. Choo; Min-Xin Guan (Human Genetics, 2005)

Cloning and Sequencing of the Growth Hormone Gene of Large Yellow Croaker and Its Phylogenetic Significance - Yun Chen; Yaping Wang; Shunping He; Zuoyan Zhu (Biochemical Genetics, 2004)